Risk assessment for varicose veins among city Police-A cross sectional study - Ramesh Timilsina; M.R. Prasad; Mubashir Angolkar; Nagaraj Patil (Elsevier, 2021)
Introduction: People with overweight, standing for prolonged time, increasing age, smoking habit, heavy lifting and pregnancies in female increases risks of having varicose veins and are found common in lower limbs i.e saphenous vein. Objective: To assess the risks of varicose vein among policemen and to assess the association between varicose vein and their designation among police of Belagavi city, Karnataka, India. Material and methods: A cross sectional study was conducted among 150 police personnel who were working in Belagavi city. Information was collected by using questionnaire for socio-demographic, general information and symptoms. Observational checklist was used to assess signs of VV. Results: Out of 150 participants, the mean age of participants was 39.28 years. Among them, 74.66% were male and 25.34% were female where 77 (51.30%) were Police Constable, 54 (36%) were Head Constable, 15 (10%) were ASI, 2 (1.30%) were Inspector & Sub Inspector respectively. The mean standing hour per day was found to be 6.69 h and the mean years of service was found to be 9.11 years. It was found that 14.7% of police personnel had varicose veins and 20% of them were in the risk of developing VV. Conclusion: varicose veins has significant association with religion, designation, duration of working, income, marital status, lungs problem, DVT, cardiac infract and HTN. Similarly, risk of developing varicose vein has a significant association with marital status and duration of standing.